McCune–Albright syndrome with multiple hyperfunctional endocrinopathies: diagnosis, treatment, and long-term follow-up: a case report - Zainab, Mariam J.; Khamies, Labibah L.; Baladi, Joudi; Almutairi, Nawal; Alsaheel, Abdulhameed (Frontiers in Endocrinology, 2025)
McCune–Albright syndrome (MAS) is a rare genetic disorder characterized by a triad of café-au-lait spots, fibrous dysplasia, and hyperfunctioning endocrinopathies, resulting from a mosaic mutation in the guanine nucleotide-binding protein (GNAS) gene. This case report presents the long-term follow-up of an eight-year-old girl diagnosed with MAS, who first presented at 22 months of age with skin pigmentation, hyperthyroidism, and precocious puberty, later developing additional features such as fibrous dysplasia and growth hormone excess. This complex presentation of MAS—featuring more than two hyperfunctioning endocrinopathies along with fibrous dysplasia—has rarely been described in the literature. The patient was appropriately managed with a combination of carbimazole (an imidazole), letrozole (an aromatase inhibitor), lanreotide (a somatostatin analogue), and zoledronic acid (a bisphosphonate). Notably, this is the first reported use of lanreotide in the management of MAS in a pediatric patient. This case highlights the challenges of managing MAS over an extended period, particularly when multiple endocrinopathies are present from an early age. We describe an effective approach to treatment, emphasizing how each condition was managed while considering the interactions among the various manifestations. Given the rarity of long-term follow-up reports, this case provides valuable insights into the management of MAS in pediatric patients with complex, multisystem presentations.